The Influence of Health Education using Video Media on Knowledge and Attitudes Related to Dental and Oral Health - Muliana, Nur; Ardyanti, Dian; Tonapa, Emelia (PT FORMOSA CENDEKIA GLOBAL, 2024)
The results of Basic Health Research (Riskesdas) in 2018 stated that the largest proportion of dental problems in Indonesia were damaged/caved/sick teeth (45.3%). East Kalimantan is ranked 12th highest out of 34 provinces in terms of the proportion of dental and oral health problems. The aim of the research is to analyze the influence of health education using videos on knowledge and attitudes related to dental and oral health at SDN 002 Loa Janan. This type of research uses a quasi-experimental design with purposive sampling technique. The research sample was 58 with data collection carried out by filling out questionnaires, with univariate and bivariate analysis. Based on the results of research using the Wilcoxon test showing a p-value of 0.000 (p>0.05). This means that there is an influence before and after being given health education using video media on the knowledge and attitudes of respondents.